2013
DOI: 10.1111/jace.12319
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Reduced Polycrystalline Sr0.5Ba0.5Nb2O6 Fabricated Via Solution Combustion Synthesis

Abstract: The thermoelectric properties of bulk polycrystalline Sr0.5Ba0.5Nb2O6 (SBN50) fabricated via solution combustion synthesis (SCS) and reduced at temperatures of 900°C–1150°C were explored. The Seebeck coefficient (S) of all samples increased over the entire range of testing temperatures; a peak S value of −281 μV/K was obtained at 930 K for the sample reduced at 900°C. A metal‐insulator transition was observed in the electrical conductivity (σ) of samples reduced at 1000°C–1150°C, whereas only semiconducting el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…and Dandeneau et al. in sufficiently reduced unfilled SBN via electron energy loss spectroscopy and in X‐ray photoelectron spectroscopy, respectively . In SBN and BNO, oxygen vacancies are necessary in that they are suspected to be electronically compensating and thus responsible for the mixed valence state in the Nb.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…and Dandeneau et al. in sufficiently reduced unfilled SBN via electron energy loss spectroscopy and in X‐ray photoelectron spectroscopy, respectively . In SBN and BNO, oxygen vacancies are necessary in that they are suspected to be electronically compensating and thus responsible for the mixed valence state in the Nb.…”
Section: Resultssupporting
confidence: 55%
“…Indeed, the presence of Nb 4+ has been reported by Lee et al and Dandeneau et al in sufficiently reduced unfilled SBN via electron energy loss spectroscopy and in X-ray photoelectron spectroscopy, respectively. 18,29 In SBN and BNO, oxygen vacancies are necessary in that they are suspected to be electronically compensating and thus responsible for the mixed valence state in the Nb. In BTNO, the mixed valence is manifest by the 2 Ti 4+ in which the oxygen vacancy concentration is negligible.…”
Section: Filled Barium End-member Stabilitymentioning
confidence: 99%
“…Several candidate ceramic p-type materials have been investigated including calcium cobaltite, Ca 3 Co 4 O 9 . There are limited studies on n-type ceramics, one promising candidate being (Sr(Ba) Nb 2 O 6 ) (Dandeneau et al 2013). Current and potential applications for TE ceramics include the recovery of waste heat in industrial furnaces or incineration processes and the harnessing of electric energy from alternative renewable energy sources such as solar thermal or geothermal.…”
Section: Emerging Energy Conversion Approachesmentioning
confidence: 99%
“…SBN was initially studied for its electro‐optic properties in its unreduced or doped forms. Recent work has now demonstrated that reduced SBN displays high electrical conductivity, a high Seebeck coefficient, and low thermal conductivity along the c ‐axis of polarization, making it an interesting candidate for thermoelectric applications. In the present paper, we have used Raman spectroscopy to identify the structural changes induced by the reduction process that introduces charge carriers.…”
Section: Introductionmentioning
confidence: 99%